The determinant of hotel quality service toward customer satisfaction : a study at Hotel UiTM Dungun / Mohamed Irfan Roslan - Roslan, Mohamed Irfan (2014)
This paper use to study the relationship between service quality and customer satisfaction in Hotel UiTM Dungun, Terengganu. The conceptual model is adopted based on the service quality model (SERVQUAL) which measures various dimensions of service quality and their relationship to customer satisfaction. Researcher use the tangibility, reliability and responsiveness dimension. These dimensions is then tested using the data that are collected in the hotel. The objective is to know the relationship between tangibility, reliability and responsiveness toward the customer satisfaction and determine the most significant variables for the customer satisfaction. Researcher use the questionnaire method to collect the data. The result from the correlation analysis state that all of the independent variables have strong correlation with the customer satisfaction. From the regression analysis also found the best predictor/variable is the tangibility dimension. From the regression also only two variables is significant which is the tangibility and responsiveness. This research can give improvement to the growing literature on the hotel industry and tourism in Malaysia.